The 26th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2004.1404262
|View full text |Cite
|
Sign up to set email alerts
|

A dual-task approach to the evaluation of the myokinemetric signal as an alternative to EMG

Abstract: EMG is the signal widely used in neuromuscular control, biofeedback and measurement applications. Alternative physiological signals are available, but are used relatively infrequently. In the development of assistive devices, such as functional electrical stimulators, it is important to make the device as straightforward to use as possible. This is particularly relevant for patients with neurological and often associated cognitive impairments. Different physiological signals may require different degrees of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A protocol similar to that reported by Canderle et al (2004) was adopted. It comprised a series of 1-D visuomotor cancellation tests presented on a computer screen.…”
Section: Experiments Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…A protocol similar to that reported by Canderle et al (2004) was adopted. It comprised a series of 1-D visuomotor cancellation tests presented on a computer screen.…”
Section: Experiments Protocolmentioning
confidence: 99%
“…Therefore, it suggests that the relationships between the neural activity and measured signal may determine both the control accuracy and the degree of attention required. A few studies have been reported to investigate the differences between two muscle signals for prosthesis motor control purposes (Canderle et al 2004). In this study, we attempted to compare the performances of 1-D SMG and surface EMG in terms of accuracy and cognitive requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative biosensors, like myokinemetric sensors [3], [4], mechanomyographic sensors [5] and accelerometers [6] have been used for upper limb pattern recognition in more general terms but have not produced accuracies acceptable for prosthetic use.…”
Section: Introductionmentioning
confidence: 99%